Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Komik pada Pelajaran Pendidikan Kewarganegaraan (PKn) Kelas X SMA Negeri 1 Jayapura - Yurenius B. Makayan (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2021)
The main objective of the research is to design an effective LKPD through comics in Civic Education (PKn) lessons in class X SMA Negeri 1 Jayapura. R&D is the method used with the ADDIE model. The results obtained showed that the application of comic-based LKPD was able to increase students' motivation and understanding of Civics Education material. Hopefully, this research can contribute to the development of innovative and interesting learning media for students.